2017
DOI: 10.31729/jnma.3283
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Oral Mucosal Lesions in a Tertiary Care Dental Hospital of Kathmandu

Abstract: Introduction: Oral mucosa can be affected by a variety of soft tissue lesions and conditions. Benign as well as malignant lesions of oral cavity are common. Squamous cell carcinoma is one of the commonest malignancies. The present retrospective study was undertaken to study the prevalence of various oral mucosal lesions in a tertiary care dental hospital of Kathmandu. Methods: This retrospective study was carried out in the Department of Oral and Maxillofacial Pathology at Kantipur Dental College and Tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 5 publications
(7 reference statements)
3
10
1
Order By: Relevance
“…In this study, inflammatory diseases were the most common group, slightly outnumbering benign neoplasms. A similar finding has been reported in many studies [2,[6][7][8][9], while in others benign neoplasms were more common [10][11]. Interestingly, oral lichen planus was the most common inflammatory condition in this study (18%), exceeding what was reported in Türkiye (11.9%) and Kuwait (4.6%) [6,12].…”
Section: Discussionsupporting
confidence: 90%
“…In this study, inflammatory diseases were the most common group, slightly outnumbering benign neoplasms. A similar finding has been reported in many studies [2,[6][7][8][9], while in others benign neoplasms were more common [10][11]. Interestingly, oral lichen planus was the most common inflammatory condition in this study (18%), exceeding what was reported in Türkiye (11.9%) and Kuwait (4.6%) [6,12].…”
Section: Discussionsupporting
confidence: 90%
“…In the study of Baharvand et al 24 , the most common sites were buccal mucosa, lip mucosa, and ventral surface of the tongue. In the study of Ghanaei et al 25 , the most common lesions were in the tongue and gums, in the study of Cury et al 26 in the gums, in the study of Ali and Bajacharya et al 28 in the buccal and gingival mucosa, and in the study by Shulman et al 29 in the palate and gums. The reason for the differences between the research results can be attributed to the different societies.…”
Section: Discussionmentioning
confidence: 94%
“…The prevalence of oral lesions is primarily determined through population-based studies, 14 , 15 , 16 , 17 , 18 or studies carried out in dental centers 19 , 20 , 21 or from oral pathology laboratories. 22 , 23 , 24 However, as no standardization in OOPML classification exists, with studies classifying OOPML by a lesion group (e.g., non-neoplastic lesions) 19 or by a specific disease (e.g., oral lesions in syphilis), 25 the reported OOPML frequencies are directly influenced.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the OOPML locations in other epidemiological surveys varied according to the diseases observed. 13 , 14 , 20 , 21 , 32 It is worth noting that the anatomical division of the oral cavity/oropharynx between studies is not standardized. 6 , 9 , 13 As an example, the soft palate, considered as an oral cavity subsite by some authors, 6 , 13 , 21 was considered as oropharynx in the present study based on TNM anatomical division criteria.…”
Section: Discussionmentioning
confidence: 99%